Experiences in implementing uHTS--cutting edge technology meets the real world. - Gribbon, P; Schaertl, S; Wickenden, M; Williams, G; Grimley, R; Stuhmeier, F; Preckel, H; Eggeling, C; Kraemer, J; Everett, J; Keighley, W; Sewing, A (2004)
Driven by growing corporate compound files, the demands of target biology, and attempts to cut cost, the number of solutions to HTS has spiralled. In quick succession new assay technologies and screening platforms are appearing on the market, with the promise of screening faster than ever in low volume high density formats whilst providing high quality data. Within this world of rapid change, Pfizer has applied cutting edge technology to HTS by introducing screening in 1 microl formats utilising single molecule detection technology. Instead of resource intensive in-house development, Pfizer entered into a collaboration with Evotec OAI / Evotec Technologies and introduced their Mark-II EVOscreen platform. In this article we will outline the benefits of the approach taken at Pfizer, Sandwich, and introduce the Mark-II EVOscreen platform, illustrating the potential but also possible pitfalls of HTS miniaturisation.